Nilai Perusahaan Pada Perusahaan Sektor Property Dan Real Estate Dilihat Dari Profitabilitas Dan Ukuran Perusahaan - Brillian Bintang Philana; R Taufik Hidayat (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2023)
Objective: This study aims to determine the effect of profitability and firm size on firm value. Design/methodology/approach: This study uses quantitative data, the sample in this study is a property and real estate sector company listed on the Indonesia Stock Exchange in the 2018-2022 period as many as 16 companies. The analysis technique used to test the hypothesis is multiple regression analysis using Eviews 9 software. Findings: The results of this study indicate that the profitability variable has a positive and statistically insignificant effect on firm value and the firm size variable has a negative andstatistically significant effect on firm value. Originality/value: This study discusses firm value and other factors such as profitability and firm size that focus on property and real estate sector companies. This study uses Price BookValue (PVB) as a measurement of firm value.